Efficacy of Microneedling Combined With Local Application of Human Umbilical Cord-Derived Mesenchymal Stem Cells Conditioned Media in Skin Brightness and Rejuvenation: A Randomized Controlled Split-Face Study - Liang, Xuelei; Li, Jiaying; Yan, Yan; Xu, Yongsheng; Wang, Xiujuan; Wu, Haixuan; Liu, Yi; Li, Linfeng; Zhuo, Fenglin (Frontiers in Medicine, 2022)
Background: Fighting skin aging signs is one of the major challenges of the 21st century, recently, mesenchymal stem cells (MSCs) and microneedling (MN) have been applied for anti-aging. This study aims to evaluate the efficacy of the combination MN and human umbilical cord-derived mesenchymal stem cells conditioned media (hUC-MSCs-CM) in skin brightness and rejuvenation. Methods: Thirty volunteers with facial skin aging were recruited for the randomized, controlled split-face study. The left and right sides of the face were randomly applied with saline via MN or hUC-MSCs-CM via MN. Five sessions were performed for each volunteer at two-week intervals. Two dermatologists evaluated the clinical improvement, in terms of skin brightness and texture. A satisfaction score based on a self-evaluation questionnaire was recorded at two weeks after the last treatment. The objective evaluation was recorded before the first treatment, and at two weeks after the last treatment. Results: Twenty-eight volunteers with a mean (SD) age of 41 (6.54) years old completed the trial. The investigator’s assessment for skin brightness and texture, and the self-satisfaction score revealed statistically better effects in the hUC-MSCs-CM -plus-MN group, when compared to the MN-saline group. No severe side effects were reported during the whole study period. The objective assessment revealed significant improvements in skin brightness (reduced melanin index, ultraviolet spots and brown spots) and skin texture (reduced wrinkles and pores, and increased skin elasticity) in the hUC-MSCs-CM-plus-MN group, when compared to the saline-MN group, while there was no obvious difference in skin hydration, trans-epidermal water loss and the erythema index. Conclusions: The combination of hUC-MSCs-CM and MN exhibited anti-aging efficacy, and this can possibly be used for facial rejuvenation in the future.